“Andrea Palladio e la Villa Veneta. Da Petrarca a Carlo Scarpa”, un viaggio alla scoperta della civiltà della villa. (I) - Giulia Tettamanzi (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The exposition “Andrea Palladio e la Villa Veneta. Da Petrarca a Carlo Scarpa” (Andrea Palladio and the villa veneta. From Petrarca to Carlo Scarpa) offers a trip through the history of the villa, in places of time, space and culture. The exposition crosses the seven centuries of the villa civilisation, suggests an itinerary of the most celebrated villas in Veneto, and has the start point in the latin culture. In this contest, we’ll explore, in latin authors original texts and in art-works showed, the typolocigical, ideological, literary archetypes of the villa, discovering the landscape relationship, read in the ancient Rome. Palladio is the concrete and conceptual centre of the exposition, and in his work, we’ll find the same ideological elements of the villa, grow up in latin culture. This text, divided in two parts, proposes, in this first piece, the born, the consolidation, the growth of the myth of an idea, that from the ancient Rom till today, doesn’t cease amazing end evolving.